Nova krajnska in Breznikova stoletna pratika - Bošnjak, Blanka (Slavia Centralis, 2020)
NOVA KRAJNSKA AND BREZNIK’S STOLETNA PRATIKAThe beginnings of the first Slovene almanac published periodically dates back at least to 1725, when the Ljubljana printer Janez Jurij Mayr published and printed the Nova krajnska pratika for 1726, while the first preserved copy dates back to 1741. The more demanding, extensive and richer Slovene almanac at the turn of the century was Večna pratika gospodarstva by Anton Breznik, which was first published in 1789 (then in several editions) and is considered the first true economic almanac in the Slovene language.
Keywords: almanac; Nova krajnska pratika; stoletna pratika; Večna pratika od gospodarstva